Understanding Agrochemical Overuse in Bangladesh: Evidence from Farmers in Naogaon District - Alam, Md Shamsul; Kiron, Md Asduzzaman (Food, Agriculture and Natural Resources - NETWORKS, 2025)
The increasing use of agrochemicals, including pesticides and fertilizers, has significantly enhanced agricultural productivity in Bangladesh. However, excessive application has resulted in severe environmental and health consequences, such as soil degradation, biodiversity loss, and human health risks. This study examines the extent and determinants of agrochemical overuse in the Naogaon district using primary data from 87 randomly selected farmers surveyed through structured questionnaires. Descriptive statistics and Ordinary Least Squares (OLS) regression analysis indicate that all respondents exceed recommended dosages, with overuse particularly prevalent in staple crops like rice, potatoes, and onions. Key drivers include increasing pest attacks (96.7%), high disease prevalence (96.7%), declining soil fertility (100%), and expectations of higher yields (70%). Additionally, 46.7% of farmers perceive recommended dosages as inadequate for pest control, while 56.7% report limited access to organic alternatives. Regression results show that education and farm size negatively influence agrochemical use, whereas age, farming experience, and household income positively correlate with higher application levels. The findings highlight the need for stringent policy interventions, including stricter agrochemical regulations, farmer education programs, and the promotion of sustainable agricultural practices.